Association of general and central adiposity with blood pressure among Chinese adults: results from the China National Stroke Prevention Project. Issue 12 (December 2018) - Fu, Wenning; Cao, Shiyi; Liu, Bing; Li, Haibin; Song, Fujian; Gan, Yong; Li, Wenzhen; Opoku, Sampson; Yan, Shijiao; Yue, Wei; Yan, Feng; Wang, Chao; et al.
Abstract : Background: The American Heart Association concluded that waist circumference was a better predictor of blood pressure risk than BMI in Asians. However, data are inconsistent and information in Chinese, the largest global population group, is limited. Methods: Data was obtained from the Chinese National Stroke Prevention Project Survey of a nationally representative sample of middle-aged and older Chinese adults. A total of 135 825 individuals not taking any antihypertensive drugs were included in this study. Multiple linear regression analyses were conducted to examine the association between blood pressure and parameters of general adiposity, including BMI, height-adjusted weight, and parameters of central adiposity, including waist circumference, hip circumference, waist–hip ratio, and waist–height ratio. Results were shown as mean difference in blood pressure associated with one standard deviation higher level of adiposity. Results: The overall means ± standard deviation of BMI and waist circumference were 24.3 ± 3.18 kg/m 2 and 84.0 ± 8.88 cm, respectively. BMI seemed more strongly associated with SBP/DBP (4.22 mmHg/SD; 2.60 mmHg/SD) than central adiposity markers. In addition, there were sex differences. For men, waist circumference showed a stronger association with SBP/DBP than BMI (4.04 vs. 3.79, P < 0.05; 2.26 vs. 2.13, P < 0.05). For women, BMI was more closely related to SBP/DBP than central adiposity parameters, such as waist circumference (4.59 vs. 3.41, P < 0.05; 2.98 vs. 2.24, P < 0.05). Additionally, in both urban and rural areas, waist circumference was mostly associated with SBP/DBP among men, whereas it was BMI among women. Conclusion: Compared with central adiposity, blood pressure is more strongly associated with general adiposity in Chinese adults. Interestingly, there are significant sex differences in the relationship of blood pressure with general and central adiposity. Waist circumference is the strongest predictor for men but suboptimal for women, and BMI tend to a better predictor of blood pressure for women. In addition, our results for men are consistent with the recommendation of the American Heart Association in 2015 that waist circumference could be used for assessing the risk of blood pressure. Abstract : Supplemental Digital Content is available in the text